Thermal haloes around plume tails - Sleep, Norman H. (Geophysical Journal International, 2004)
The inward flow of ambient mantle material can cause thermal haloes around plume tail conduits to be narrow. The plume is hard to detect tomographically within depth ranges where such flow occurs. This may occur in the transition zone beneath Iceland. The influx rate per length of conduit needs to be of the order of 25 × 10−6 m2 s−1 to have noticeable effects. Such flow rates would quench weak plumes but not greatly perturb strong ones. A pressure deficit of the plume conduit of several MPa would drive this flow if the mantle viscosity did not exceed 1022 Pa s.